2020
DOI: 10.1017/s0016756820001090
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal magmatism produced by delamination: geochemical evidence from late Palaeozoic volcanic rocks from the Yili Block, Western Tianshan, Northwestern China

Abstract: The Western Tianshan orogenic belt is essential for understanding the evolution of the Central Asian orogenic belt. However, no agreement exists among geologists about its tectonic environment during the Late Palaeozoic. The volcanic rocks of the Yishijilike and Wulang Formation in the Yili Block, Western Tianshan, formed in the Late Carboniferous to Early Permian, mainly consist of a bimodal suite of basalts – basaltic andesites and rhyolites, with only some intermediate rocks. Mafic rocks are slightly enrich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 73 publications
(101 reference statements)
0
2
0
Order By: Relevance
“…In this context, the Carboniferous magmatism has been extensively studied with various hypotheses. It was considered to develop in an intracontinental rift setting (Xia et al 2012;Xia and Li 2020), a continental arc setting (An et al 2013;Tang et al 2013;Wang et al 2007b;Yu et al 2016;Zhong et al 2017;Zhu et al 2009), a postcollisional setting (Chen et al 2020;Feng and Zhu 2019;Ge et al 2015;Long et al 2012;Sun et al 2008) or a back-arc extensional setting (Cao et al 2017;Qian et al 2006;Su et al 2018;Wang et al 2018aWang et al , b,2019Yan et al 2015) on the basis of geochemical features of different studied targets. These complex Carboniferous magmatic rocks were subdivided into four main belts, from north to south, as the Keguqinshan-Tulasu, Awulale, Wusun Mountain and Haerk-Nalati domains, according to their geographical distribution characteristics (e.g.…”
Section: Geodynamic Implication: Back-arc Extension In the Yili-central Tianshan Blockmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, the Carboniferous magmatism has been extensively studied with various hypotheses. It was considered to develop in an intracontinental rift setting (Xia et al 2012;Xia and Li 2020), a continental arc setting (An et al 2013;Tang et al 2013;Wang et al 2007b;Yu et al 2016;Zhong et al 2017;Zhu et al 2009), a postcollisional setting (Chen et al 2020;Feng and Zhu 2019;Ge et al 2015;Long et al 2012;Sun et al 2008) or a back-arc extensional setting (Cao et al 2017;Qian et al 2006;Su et al 2018;Wang et al 2018aWang et al , b,2019Yan et al 2015) on the basis of geochemical features of different studied targets. These complex Carboniferous magmatic rocks were subdivided into four main belts, from north to south, as the Keguqinshan-Tulasu, Awulale, Wusun Mountain and Haerk-Nalati domains, according to their geographical distribution characteristics (e.g.…”
Section: Geodynamic Implication: Back-arc Extension In the Yili-central Tianshan Blockmentioning
confidence: 99%
“…Complex subduction and accretion processes took place during the aforementioned period, producing massive Late Paleozoic magmatism in the western Chinese Tianshan, which is well recorded in a series of widespread Carboniferous volcanic rocks (XBGMR 1993). Previous studies suggested that they were formed in an intracontinental rift setting (Xia et al 2012;Xia and Li 2020), a continental arc setting (An et al 2013;Tang et al 2013;Wang et al 2007b;Yu et al 2016;Zhong et al 2017;Zhu et al 2009), a post-collisional setting (Chen et al 2020;Feng and Zhu 2019;Ge et al 2015;Long et al 2012;Sun et al 2008;Xiao et al 2010) or a back-arc extensional setting (Cao et al 2017;Qian et al 2006;Su et al 2018;Wang et al 2018aWang et al , b, 2019Yan et al 2015). Due to these controversial interpretations, their tectonic setting, and especially the implication that they have for the formation of the Kazakhstan Orocline, still warrant further elaboration.…”
Section: Introductionmentioning
confidence: 99%